A study of "Magic of vicinity" in childhood poetry(Based on work's of Naser keshavarz_Kazem mazinani and Shokooh ghasem nia) - latife sakhavi; Mona Alimadadi; Hosein Mohammadi (مطالعات زبانی و بلاغی)
One of the main topics of traditional rhetoric is the impact of speech on the audience. Accordingly, the more rhetorical the speech is, the more influential it is on the audience. Observance of addressee’s circumstances and positions should certainly be considered by a poet(ess) or an author in order to transfer his/her thought or passion to the audience in the best way. To do so, there are varied tools and methods. One of the most effective tools is to strike a balance in the phonetic chain of words or the vocabulary chain of sentences. This balance and coordination as well as the role speech musical plays on the audience is called "the magic of vicinity". Works in which “form” is more important than the “meaning” can be examined from this perspective. (Examining the types of balances and their role in influencing the audience). Among the various types of literature, children poetry has such an ability because of its well-formed nature. In this research, the writers' effort has been to study the magic of vicinity in child poetry using the formalist method and show which types of balances (phonetic, lexical, and syntactical) exist more in it. Further, the research attempts to demonstrate why and how these balances affect the audience (children).The findings of this study show that: 1. There are a variety of phonetic, lexical, and syntactic equations (albeit with different frequencies) in child poems. 2. Nonsense elements that do not play a role in the meaning of poetry are considered as an effective factor in musical compilation in child poetry. 3. As the game for a child is the living itself (according to Jean Piaget, a child psychology theorist), and the child learns everything from the childish games, poetry and a variety of equilibrium, which can be considered as language games, are a suitable platform for the child's education and intellectual development.